Clinical and Microbiological Profile of HIV/AIDS Cases with Diarrhea in North India. (27th December 2012) - Jha, Arun Kumar; Uppal, Beena; Chadha, Sanjim; Bhalla, Preena; Ghosh, Roumi; Aggarwal, Prabhav; Dewan, Richa
Abstract : Intestinal infections are a significant cause of morbidity and mortality in people living with HIV/AIDS (PLWHA) especially in developing countries. The present study was conducted to assess the clinical and microbiological spectrum in HIV/AIDS cases with diarrhea and to correlate the occurrence of such pathogens with stool characters, HIV seropositivity status, and CD4 counts. Stools from 154 HIV seropositive subjects and 50 HIV negative controls were examined by direct microscopy, fecal cultures, and serological tests ( Clostridium difficile Toxin A, Cryptosporidium antigen, and Entamoeba histolytica antigen ELISA). CD4 T cell enumeration was done using FACS count (Becton Dickinson). The study showed a male preponderance (112 males and 42 females). Weakness, abdominal pain, and anorexia were the most common symptoms. Coccidian parasites were the most common cause of diarrhea in HIV seropositive cases. C. parvum was seen in 60.42% while Isospora belli in 9.03%. Amongst the bacterial pathogens C. difficile was detected in 18.06%, diarrheagenic Escherichia coli in 11.11%, and Shigella spp. in 2.78%. Pathogen isolation rates were more in HIV seropositive cases and subjects with low CD4 T lymphocyte counts. Regular monitoring of CD4 T lymphocyte counts and screening for enteric pathogens will help improve the quality of life for PLWHA.